EXPORT MARKET ORIENTATION, INNOVATION AND PERFORMANCE OF FRUIT EXPORTING FIRMS IN UGANDA - Ahimbisibwe, Godwin. M.; Ntayi, Joseph M.; Ngoma, Muhammed (European Scientific Journal, ESJ, 2013)
﻿﻿﻿The purpose of this study was to investigate the impact of export market orientation, innovation on the export performance of fruit exporting firms in Uganda. The study was prompted by the fact that Uganda’s fruit exports were growing marginally when compared to other fruit exporting countries in the COMESA region. And it wasn’t clear whether this trend could be attributed to low levels of export market orientation and innovativeness that seemed to characterise most of the fruit exporting firms in Uganda, besides research on export market orientation, innovation and export performance is disappointingly scarce in Uganda. Therefore, a quantitative cross sectional research design was adopted to undertake the study. A field study using simple random sampling was used to select a sample of 56 firms whose 3 top executives were key informants. Correlation analysis was carried out on the study and the findings revealed a significant positive between innovation, market orientation and export performance of fruit exporting firms in Uganda which confirmed earlier submissions by previous researchers. However when a regression model was conducted, it was observed that innovation was a significant predictor of export performance while export market orientation wasn’t. It was therefore recommended that fruit exporting firms in Uganda should focus more on innovation if they are to enhance their export performance.